Vaccine-induced humoral response against SARS-CoV-2 dramatically declined but cellular immunity possibly remained at 6 months post BNT162b2 vaccination - Kato, Hideaki; Miyakawa, Kei; Ohtake, Norihisa; Yamaoka, Yutaro; Yajima, Satoshi; Yamazaki, Etsuko; Shimada, Tomoko; Goto, Atsushi; Nakajima, Hideaki; Ryo, Akihide (Vaccine, 2022)
•Both IgG against spike protein (SP IgG) and 50% neutralizing antibody markedly decreased at 6-month post-vaccination.•SP IgG titer had a negative correlation with age and alcohol consumption, but cellular immunity did not correlate with these factors.•SP IgG titer against the Delta strain was 60% of that against the original strain but increased to 90% in the subjects with breakthrough infection.•Cellular immunity was observed despite the substantial decrease in antibody titer after vaccination, suggesting their sequential dynamics differed. To evaluate vaccine-induced humoral and cell-mediated immunity at 6 months after completion of two doses of BNT162b2 vaccination, immunoglobulin G against SARS-CoV-2 spike protein (SP IgG), 50% neutralizing antibody (NT50), and spot-forming cell (SFC) counts were evaluated by interferon-γ releasing ELISpot assay of 98 healthy subjects (median age, 43 years). The geometric mean titers of SP IgG and NT50 decreased from 95.2 (95% confidence interval (CI) 79.8–113.4) to 5.7 (95% CI 4.9–6.7) and from 680.4 (588.0–787.2) to 130.4 (95% CI 104.2–163.1), respectively, at 3 weeks and 6 months after the vaccination. SP IgG titer was negatively correlated with age and alcohol consumption. Spot-forming cell counts at 6 months did not correlate with age, gender, and other parameters of the patients. SP IgG, NT50, and SFC titers were elevated in the breakthrough infected subjects. Although the levels of vaccine-induced antibodies dramatically declined at 6 months after vaccination, a certain degree of cellular immunity was observed irrespective of the age.